THE ASSOSIATION BETWEEN HIV AND AIDS KNOWLEDGE AND UPTAKE OF HIV TESTING AMONG SEXUALLY ACTIVE YOUNG POPULATION AGE 15-24 IN DISTRICT MERAUKE, PAPUA PROVINCE, INDONESIA - Nurul Azmi (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: This study examine relationship between HIV and AIDS knowledge as one of milestone to uptake HIV testing. Knowledge was first step as response to HIV prevention. Young population was the vulnerable group who were in stage of exploring sexual experience and had less awareness of personal risk. Aims: The aim of this study is to determine the distribution of HIV and AIDS knowledge and to know its association with response to HIV testing among young population who have had sex in the last 12 months preceding the survey. Method: Data set were obtained from Multiple Indicator Cluster Survey (MICS) 2011. Respondents consist of 119 young women and 56 young men age 15-24 years old who lived in Merauke adminstrative area.Comprehensive HIV and AIDS knowledge was measured from at least gave 6 correct answers from 7 questions. Data output are analyzed by cross-tabulation to describe socio demographic, HIV and AIDS knowledge and HIV testing and bivariat analysis to know their correlation. Results: HIV and AIDS knowledge was in low level (28%). Respondent who have been tested in last 12 months preceding the survey have tiny participant (10,3%). Women, higher education, non- Papua ethnicity, and wealth status were all positively associated with having comprehensive knowledge. And only wealth status significantly associated with HIV testing. Substantively, young people who had comprehensive knowledge are more likely to uptake HIV testing, but in this paperit didn’t significantly proved. Conclusion: HIV and AIDS knowledge among young population in Merauke was very poor status and it significantly impact to lack of uptake in HIV testing.To know HIV status, there are many approaches to drive people and knowledge is one of milestone to start. The uptake of HIV testing were more likely has done among young population who had good knowledge about HIV and AIDS.